KEPENTINGAN JEPANG MEMBATASI EKSPOR BAHAN BAKU SEMIKONDUKTOR KE KOREA SELATAN - Lukluk Nurbaiti; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The study analyzed Japan's interest in issuing a policy restricting the export of semiconductor raw materials to South Korea. The policy originated with South Korea's Supreme Court ruling that three Japanese companies paid compensation to the families of victims of forced labor during the Japanese occupation. The three companies are companies engaged in the semiconductor manufacturing industry.  This study uses a Neo-merchantilisme perspective that focuses on the country's efforts to profit by providing barriers to international trade against other countries. The theory used is trade theory: a diamond model with a foreign policy concept. Based on internal and external factors, Japan updated security export control rules that tighten the export process of certain items based on FEFTA rules. Tightened items include semiconductor raw materials. This rule applies to white-listed countries, including South Korea.Keywords: Interests, Export Restrictions Policy, Semiconductor Raw Materials